Mark: a commentary - Collins, Adela Yarbro (Hermeneia - a critical and historical commentary on the Bible, 2007)
Adela Yarbro Collins's remarkably learned and thorough introduction to and exposition of Mark's Gospel deserves a prominent place in every serious theological library. It provides us solid information not only about Markan studies but also about the Jewish and Greco-Roman world in which that Gospel took shape. It is a great achievement, the product of many years of dedicated research. --Daniel J. Harrington, Weston Jesuit School of Theology